Group Living and Male Dispersal Predict the Core Gut Microbiome in Wild Baboons. (29th September 2017) - Grieneisen, Laura E.; Livermore, Josh; Alberts, Susan; Tung, Jenny; Archie, Elizabeth A.
Synopsis: The mammalian gut microbiome plays a profound role in the physiology, metabolism, and overall health of its host. However, biologists have only a nascent understanding of the forces that drive inter-individual heterogeneity in gut microbial composition, especially the role of host social environment. Here we used 178 samples from 78 wild yellow baboons ( Papio cynocephalus ) living in two social groups to test how host social context, including group living, social interactions within groups, and transfer between social groups (e.g., dispersal) predict inter-individual variation in gut microbial alpha and beta diversity. We also tested whether social effects differed for prevalent "core" gut microbial taxa, which are thought to provide primary functions to hosts, versus rare "non-core" microbes, which may represent relatively transient environmental acquisitions. Confirming prior studies, we found that each social group harbored a distinct gut microbial community. These differences included both non-core and core gut microbial taxa, suggesting that these effects are not solely driven by recent gut microbial exposures. Within social groups, close grooming partners had more similar core microbiomes, but not non-core microbiomes, than individuals who rarely groomed each other, even controlling for kinship and diet similarity between grooming partners. Finally, in support of the idea that the gut microbiome can be altered by current social context, we found that the longer an immigrant male had lived in a given social group, the more closely his gut microbiome resembled the gut microbiomes of the group's long-term residents. Together, these results reveal the importance of a host's social context in shaping the gut microbiome and shed new light onto the microbiome-related consequences of male dispersal.